Simultaneously Enhancing Thermal Stable Dielectric Property and Piezoelectric Response in Lead-Free LiNbO3-Modified (K0.5Na0.5)NbO3- (BaNi0.5Nb0.5O3) System - Ji, Hongfen; Xin, Lipeng; Ma, Han; Liu, Weiguo; Dai, Zhonghua; Pang, Lixia; Xie, Jinglong; Chen, Zhaobin (Frontiers in Materials, 2020)
Perovskite ferroelectic oxides with simultaneous highly thermal stable dielectric property and piezoelectric response are promising candidate for advanced energy, dielectric, and smart devices. The (1-x)[0.98[(K0.5Na0.5)NbO3]-0.02(BaNi0.5Nb0.5O3)]-xLiNbO3 (abbreviated as (1-x)KNBNNO-xLiNbO3; x = 0.00, 0.02, 0.04, 0.06, 0.08) lead-free multifunction ferroelectric ceramic is synthesized by solid-state reaction method. XRD analysis reveals that the samples exhibit perovskite structure with 0≤x≤0.06, and the second phase K3Li2Nb5O15 appears at x=0.08. The scanning electron microscopy image show that the grain size of ceramics increases from 0.65 μm to 3.58 μm with LiNbO3 content increasing. Meanwhile, the Curie temperature (TC) shifts to a higher temperature (~ 427 °C for x=0.06). A high dielectric thermal stability of ∆ε/ε40°C ≤ ±10%, with a high dielectric permittivity (~1400), is achieved at x = 0.06 over a wide temperature range of ~40–348 °C with d33 of ~160 pC·N−1, and a remnant polarization (Pr) of 20.5 μC·cm−2. This work shows that this multifunction material could be applied in sensor to efficiently covert both solar and kinetic energies into electricity over a wide temperature range.